Analysis of predictive factors of unforeseen nodal metastases in resected clinical stage I NSCLC - Gallina, Filippo Tommaso; Marinelli, Daniele; Tajè, Riccardo; Forcella, Daniele; Alessandrini, Gabriele; Cecere, Fabiana Letizia; Fusco, Francesca; Visca, Paolo; Sperduti, Isabella; Ambrogi, Vincenzo; Cappuzzo, Federico; Melis, Enrico; et al. (Frontiers in Oncology, 2023)
Background Despite notable advances made in preoperative staging, unexpected nodal metastases after sur-gery are still significantly detected. In this study we aim to analyze the upstaging rate in patients with clinical stage I NSCLC without evidence of nodal disease in the preoperative staging who underwent lobectomy and radical lymphadenectomy. Methods Patients who underwent lobectomy and systematic lymphadenectomy for clinical stage I NSCLC were evaluated. Exclusion criteria included the neoadjuvant treatment, incomplete resection and no adherence to preoperative guidelines. Results A total of 359 patients were included in the study. 172 patients were female, and the median age was 68 (61 - 72) . The variables that showed a significant correlation with the upstaging rate at the univariate analysis were the number of resected lymph nodes and micropapillar/solid adenocar-cinoma subtype. This result was confirmed in the multivariate analysis with a OR= 2.545 (95%CI 1.136-5.701; p=0.02) for the number of resected lymph nodes and a OR=2.717 (95%CI 1.256-5.875; p=0.01) for the high-grade pattern of adenocarcinoma. Conclusion Our results showed that in a homogeneous cohort of patients with clinical stage I NSCLC, the number of resected lymph nodes and the histological subtype of adenocarcinoma can signifi-cantly be associated with nodal metastasis.